“I’m truly free from my eating disorder”: Emerging adults’ experiences of FREED, an early intervention service model and care pathway for eating disorders - Rachel Potterton; Amelia Austin; Michaela Flynn; Karina Allen; Vanessa Lawrence; Victoria Mountford; Danielle Glennon; Nina Grant; Amy Brown; Mary Franklin-Smith; Monique Schelhase; William Rhys Jones; et al. (Journal of Eating Disorders, 2021)
Abstract Background Eating disorders (EDs) typically start during adolescence or emerging adulthood, periods of intense biopsychosocial development. FREED (First Episode Rapid Early Intervention for EDs) is a service model and care pathway providing rapid access to developmentally-informed care for emerging adults with EDs. FREED is associated with reduced duration of untreated eating disorder and improved clinical outcomes, but patients’ experiences of treatment have yet to be assessed. Objective This study aimed to assess emerging adults’ experiences of receiving treatment through FREED. Method This study triangulated qualitative data on participants’ experiences of FREED treatment from questionnaires and semi-structured interviews. Participants were 106 emerging adults (aged 16–25; illness duration < 3 yrs) (questionnaire only = 92; interview only = 6; both = 8). Data were analysed thematically. Results Most participants reported psychological and behavioural changes over the course of treatment (e.g. reduction in symptoms; increased acceptance and understanding of difficulties). Participants identified five beneficial characteristics of FREED treatment: i) rapid access to treatment; ii) knowledgeable and concerned clinicians; iii) focusing on life beyond the eating disorder; iv) building a support network; v) becoming your own therapist. Conclusion This study provides further supports for the implementation of early intervention and developmentally-informed care for EDs. Future service model development should include efforts to increase early help-seeking.